2019
DOI: 10.1155/2019/1941426
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solution for One-Dimensional Transport of Particles considering Dispersion in Deposition Kinetics

Abstract: The study of particle transport in porous media is of great significance for pollution mitigation, grouting reinforcement, municipal solid waste landfill management, and groundwater exploitation. We developed an analytical solution for a corrected convection-dispersion model that takes into account the effects of dispersion on deposition kinetics with regard to the particle concentration decay type. The rationality and correctness of the solution were verified using time, distance, deposition coefficient, diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The transport of suspended particles through a homogeneous porous medium with a uniform onedimensional flow is described by the convection-dispersion equation, including a term of first-order deposition kinetic [5,19,31]:…”
Section: Transport Parameters Identification Methodsmentioning
confidence: 99%
“…The transport of suspended particles through a homogeneous porous medium with a uniform onedimensional flow is described by the convection-dispersion equation, including a term of first-order deposition kinetic [5,19,31]:…”
Section: Transport Parameters Identification Methodsmentioning
confidence: 99%
“…(2b) shows the formula. 11) The adapted λ = filtration coefficient; it relates to particle-deposition. We adapted it and the formula from the study [38].…”
Section: Parameterization Of Pothole Model Equationmentioning
confidence: 99%
“…It requires applying various specific data of the roadway's subsurface and surface materials, and then different established principles. Research has shown that using detailed data, and established principles draw the prediction that makes a road deformation model closer to reality [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional continuum models for particle transport in a porous medium solve a one-dimensional convection–diffusion equation with two important modifications: (1) the diffusion coefficient is modified to account for the sum of molecular diffusion and particle dispersion, where the last term is proportional to the nominal velocity of particles within the bed, and (2) a particle sink term is included representing capture of particles by the porous medium (Benamar et al . 2007; Chen, Zhang & Wu 2019). The parameters used in continuum models (diffusion coefficient, capture rate coefficient, etc.)…”
Section: Introductionmentioning
confidence: 99%